The mood stabilizer valproate activates human FGF1 gene promoter through inhibiting HDAC and GSK‐3 activities - Kao, Chien‐Yu; Hsu, Yi‐Chao; Liu, Jen‐Wei; Lee, Don‐Ching; Chung, Yu‐Fen; Chiu, Ing‐Ming (Journal of neurochemistry, 2013)
Valproic acid (VPA) is the primary mood‐stabilizing drug to exert neuroprotective effects and to treat bipolar disorder in clinic. Fibroblast growth factor 1 (FGF1) has been shown to regulate cell proliferation, cell division, and neurogenesis. Human FGF1 gene 1B promoter (−540 to +31)‐driven green fluorescence (F1BGFP) has been shown to recapitulate endogenous FGF1 gene expression and facilitates the isolation of neural stem/progenitor cells (NSPCs) from developing and adult mouse brains. In this study, we provide several lines of evidence to demonstrate the underlying mechanisms of VPA in activating FGF‐1B promoter activity: (i) VPA significantly increased the FGF‐1B mRNA expression and the percentage of F1BGFP(+) cells; (ii) the increase of F1BGFP expression by VPA involves changes of regulatory factor X (RFX) 1‐3 transcriptional complexes and the increase of histone H3 acetylation on the 18‐bp cis‐element of FGF‐1B promoter; (iii) treatments of other histone deacetylases (HDAC) inhibitors, sodium butyrate and trichostatin A, significantly increased the expression levels of FGF‐1B, RFX2, and RFX3 transcripts; (iv) treatments of glycogen synthase kinase 3 (GSK‐3) inhibitor, lithium, or GSK‐3 siRNAs also significantly activated FGF‐1B promoter; (v) VPA specifically enhanced neuronal differentiation in F1BGFP(+) embryonic stem cells and NSPCs rather than GFP(−) cells. This study suggested, for the first time, that VPA activates human FGF1 gene promoter through inhibiting HDAC and GSK‐3 activities. We show that the mood‐stabilizing drugs, valproic acid (VPA) and Li+, could up‐regulate FGF‐1B promoter through inhibition of HDACs and GSK‐3. We further demonstrate that treatment of VPA increases histone acetylation around the regulatory region (18‐bp cis‐element) of FGF‐1B promoter. Importantly, VPA could induce more neuronal differentiation in FGF‐1B positive neural stem/progenitor cells than FGF‐1B negative cells.